The Role of Primary Care in a Pandemic: Reflections During the COVID-19 Pandemic in Canada - Joanne Kearon; Cathy Risdon (SAGE Publishing, 2020)
As COVID-19 cases began to rise in Ontario, Canada, in March 2020, increasing surge capacity in hospitals and intensive care units became a large focus of preparations. As part of these preparations, primary care physicians were ready to be redeployed to the hospitals. However, due to the effective implementation of community-wide public health measures, the hospital system was not overwhelmed. As Ontario prepares now for a potential second wave of COVID-19, primary care physicians have an opportunity to consider the full breadth and depth of scope for primary care during a pandemic. From planning to surveillance to vaccination, primary care physicians are positioned to play a unique and vital role in a pandemic. Nevertheless, there are specific barriers that will need to be overcome.